Józef Tadeusz Milik in the École Biblique (1952-1960) - Kapera, Zdzisław J. (The Biblical Annals, 2015)
J.T. Milik (1922-2006) was first of all a brilliant epigrapher and publisher of the Dead Sea Scrolls. His stay at the École Biblique marked a crucial period in his busy life. It was the golden decade in his scholarly output. He identified, deciphered and published most of the Dead Sea documents which appeared in print in the 1950s (suffice it to mention the manuscripts of 1Q and 5Q, the Copper Scroll from Cave 3, documents from Wadi Murabba‘at and some scrolls of Cave 4). He wrote a synthesis in 1957 which remains one of the most cited books on the scrolls. Starting from March 1952 Milik took part in archaeological searches at Khirbet Qumran and in the Judaean Desert. He cooperated with Father Bellarmino Bagatti at Dominus Flevit in Jerusalem. Milik discovered several Second Temple tombs with numerous ossuaries close to Jerusalem. His two expeditions with Father Jean Starcky yielded hundreds of Nabataean inscriptions. He remains in the history of Biblical research as a co-founder of Qumranology and a Biblical archaeologist par excellence.